Effect of exercise training in skeletal muscle remodeling in heart failure with preserved ejection fraction - Santos, Inês Margarida Chaves (2019)
Heart failure with preserved ejection fraction (HFpEF) is a complex clinical syndrome characterized by pulmonary congestion, dyspnea, elevated left ventricular filling pressures, normal left ventricular ejection fraction (LVEF ≥ 50%) and exercise intolerance. Although it is an increasingly common syndrome, its treatment remains quite limited, with available therapies focusing mostly on symptom relief. Intolerance to exercise training is one of the main symptoms presented by patients with HFpEF. Due to the known benefits of exercise training at cardiovascular levels, it has been recommended as adjuvant non-pharmacological therapy in the treatment of HFpEF. Indeed, the benefits of exercise training have already been documented in HFpEF, however the molecular mechanisms underlying those benefits remain poorly understood. Thus, this study aimed to study the molecular changes underlying exercise training effects in HFpEF. An animal model of HFpEF was used, namely obese ZSF1 rats. The animals were submitted to a treadmill exercise protocol for 4 weeks, after which exercise intolerance test and hemodynamic evaluation were performed. After animal sacrifice, the gastrocnemius muscle was collected for metabolic analysis by Nuclear Magnetic Resonance Spectroscopy and Western Blot protein expression evaluation. Comparison between the metabolic profiles of gastrocnemius of ZSF1 obese rats and ZSF1 lean (control) rats allowed to characterize the changes inherent to the disease. The results show that HFpEF promoted glycogen degradation in small oligosaccharides, resulting in the release of glucose-1-phosphate, as well as glucose-6-phosphate and glucose accumulation. In addition, decreased AMPK expression, impaired metabolism of ketone bodies and increased metabolism of amino acids such as glutamine and glutamate were also observed in the sedentary HFpEF group. The impact of exercise on gastrocnemius metabolism of this animal model was evaluated by comparing sedentary and exercised obese animals. The results obtained show that, as in sedentary animals, the exercised animals also showed a high rate of glycogen degradation, with no significant impact of exercise on glucose metabolism. Also, amino acid metabolism remained unchanged. However, the exercised group showed changes that suggest an increment in fatty acid betaoxidation and oxidative phosphorylation, as well as the reestablishment of ketone body metabolism. Overall, this work has shown that exercise has a positive impact on gastrocnemius metabolism thus supporting its supervised prescription to patients with HFpEF.